Development and Validation of a Proposed Hybridized Instructional Competencies and Leadership Assessment of the PAASCU - Accredited Schools in Secondary Education - Nasiad, Menere (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study developed and validated a hybridized instructional competencies and leadership assessment for PAASCU-accredited private secondary schools by integrating indicators from existing private-school teacher evaluation tools, the Philippine Accrediting Association of Schools, Colleges and Universities (PAASCU) evaluation criteria, the Philippine Professional Standards for Teachers (PPST), and teacher leadership standards. Anchored on Vygotsky’s Cognitive Development Theory, constructivist perspectives, competency-based education, teacher leadership concepts, and Expectancy Theory, the study employed a mixed method research design using the Delphi Technique and the four-phase instrument development process of planning, construction, evaluation, and validation. Teacher performance evaluation instruments from four private secondary schools were analyzed, categorized, and consolidated, while six educational experts comprising school administrators, a PAASCU member, a DepEd supervisor, and a teacher validated the proposed assessment. A four-point Likert scale, frequency distribution, and weighted mean were used to determine expert agreement. Findings showed strong agreement with both instructional competencies and instructional leadership, which obtained overall weighted means of 3.8 and 3.9, respectively. Assessment and reporting received the highest rating among instructional competency domains at 4.0, while curriculum and planning obtained the highest instructional leadership rating at 3.97. Expert recommendations resulted in the merging, rewording, reclassification, and removal of redundant or unclear indicators, producing a more concise and appropriately aligned instrument. The study concluded that the validated assessment may support teacher evaluation, professional development, instructional improvement, and leadership development in private secondary schools. Pilot implementation, further item analysis, expanded expert validation, additional statistical analysis, and testing in other private-school settings were recommended. The study supports SDG 4 (Quality Education) through its emphasis on teacher quality and professional development and SDG 17 (Partnerships for the Goals) through professional engagement and school-community collaboration. Its sustainability impact is primarily educational and institutional by supporting continuous teacher development, quality assurance, instructional improvement, professional collaboration, and sustained school improvement.
Keywords: Assessment and Reporting; Instructional Competencies; Instructional Leadership; PAASCU-Accredited Private Secondary Schools; Philippine Professional Standards for Teachers; Professional Development; Teacher Evaluation